PENGUKURAN TINGKAT KEPUASAN PENGGUNA SITUS WEB PEMERINTAH (E-GOVERNMENT) KABUPATEN BADUNG - Gerson Feoh; Putu WidaGunawan (LPPM Universitas Dhyana Pura, 2016)
ABSTRACTCurrently the Badung regency administration has had a website Electronic Government (e-Gov), butdoes not have definitive data about the data indicator of the level of user satisfaction. This study aims todetermine the extent of user satisfaction level Government website (e-Gov) Badung through measuring the level of user satisfaction using a questionnaire with a variable declaration End-User Computing Satisfaction (EUCS) and measured with a model of Kano. The sample used to determine the level of user satisfaction ratings in this study were students living in Badung as a potentia luser of the web site Government (e-Gov) Badung regency. Expected results in this study are quantitative analysis results by questionnaire to obtain the results of the calculation of the satisfaction level from website users e-Gov in Badung regency administration.Keywords: e-Government, Badung, Kano Model, EUCS (End-User Computing Satisfaction).ABSTRAKSaat ini Pemerintah Kabupaten Badung telah memiliki situs web Electronic Government (e-Gov), namun belum mempunyai data yang pasti mengenai data indicator tingkat kepuasan pengguna. Penelitian ini bertujuan untuk mengetahui sampai sejauh mana tingkat kepuasan pengguna situs web Pemerintah (e-Gov) Kabupaten Badung melalui pengukuran tingkat kepuasan pengguna menggunakan kuesioner dengan variable pernyataan End-User Computing Satisfaction (EUCS) dan diukur dengan model Kano. Sampel yang digunakan untuk mengetahui penilaian tingkat kepuasan pengguna dalam penelitian ini adalah mahasiswa yang tinggal di Kabupaten Badung sebagai pengguna potensial situs web Pemerintah (e-Gov) KabupatenBadung. Hasil yang diharapkan dalam penelitian ini adalah suatu hasil analisa secara kuantitatif dengan metode kuesioner untuk memperoleh hasil perhitungan tingkat kepuasan pengguna situs web e-Gov di Kabupaten Badung. Kata Kunci : e-Government, Kabupaten Badung, Model Kano, EUCS (End-User Computing Satisfaction).